The Effect of TNF-α on Regulatory T Cell Function in Graft-versus-Host Disease - Mancusi, Antonella; Piccinelli, Sara; Velardi, Andrea; Pierini, Antonio (Frontiers in Immunology, 2018)
FoxP3+ regulatory T cells (Tregs) are a subset of CD4+ T cells that can suppress proliferation and effector functions of T cells, B cells, NK cells, and antigen-presenting cells. Treg deficiency causes dramatic immunologic disease in both animal models and humans. As they are capable to suppress the function and the proliferation of conventional CD4+ and CD8+ T cells, Treg-based cell therapies are under evaluation for the treatment of various autoimmune diseases and are currently employed to prevent graft-versus-host disease (GvHD) in clinical trials of hematopoietic stem cell transplantation. Even though tumor necrosis factor-α (TNF-α) is well known for its pro-inflammatory role, recent studies show that it promotes Treg activation and suppressive function. In the present review, we discuss the role of TNF-α in Treg function and the possible implications on the actual treatments for immune-mediated diseases, with a particular attention to GvHD.